Life and Activity of Muhammad Shaybaniykha (Texas Journal of Multidisciplinary Studies, 2022)
Abu al-Fath Muhammad Shaybani bin Shah Badaq bin Abu al-Khairkhan, born in 1451 and descended from Genghis Khan. It was called "The King's Wealth" in his youth, and over time his nickname changed to Shaybek, a nickname he chose as an adult. His father and grandfather died when he was still young, and he spent the beginning of his life chasing one of the enemies of his brother and grandfather, Abu al-Khairkhan. And they were going with a group of knights defending themselves. During this test, he learned how to live in the darkest conditions, which made him a great leader. The scene of these events is the Kabjak Plateau, which was once the kingdom of Chaghataykhan, a descendant of Genghis Khan. He united many Uzbek tribes and laid the foundation for their rise in M. Manaron and the establishment of the Bukhara Khanate.